Toxoplasma gondii Me49 and NED strains arrest host cell cycle progression and alter chromosome segregation in a strain-independent manner - Rojas-Barón, Lisbeth; Hermosilla, Carlos; Taubert, Anja; Velásquez, Zahady D. (Frontiers in Microbiology, 2024)
Toxoplasma gondii is an obligate intracellular parasite that modulates a broad range of host cell functions to guarantee its intracellular development and replication. T. gondii includes three classical clonal lineages exhibiting different degrees of virulence. Regarding the genetic diversity of T. gondii circulating in Europe, type II strains and, to a lesser extent, type III strains, are the dominating populations, both in humans and animals. Infections with type I strain led to widespread parasite dissemination and death in mice, whilst type III is considered avirulent. Previously, we demonstrated that primary endothelial cells infected with the T. gondii RH strain (haplotype I) were arrested in the G2/M-phase transition, triggering cytokinesis failure and chromosome missegregation. Since T. gondii haplotypes differ in their virulence, we here studied whether T. gondii-driven host cell cycle perturbation is strain-dependent. Primary endothelial cells were infected with T. gondii Me49 (type II strain) or NED (type III strain) and their growth kinetic was compared covering until tachyzoites ruptured the monolayer (6-30 h p. i.). Here, only slight differences in the onset of full proliferation were observed and developmental data in principle matched those of the RH strain. FACS-based DNA quantification to estimate cell proportions experiencing different cell cycle phases (G0/1-, S- and G2/M-phase) revealed that Me49 and NED strains both arrested the host cell cycle in the S-phase. Cyclins A2 and B1 as key molecules of S- and M-phase were not changed by Me49 infection whilst NED infection induced cyclin B1 upregulation. To analyze parasite-driven alterations during mitosis, we here demonstrated that Me49 and NED infections both led to impaired host cellular chromosome segregation and irregular centriole overduplication. Moreover, in line with the RH strain, both strains boosted the proportion of binucleated cells within infected endothelial cell layers thereby indicating enhanced cytokinesis failure. Taken together, we here show that all, parasite-driven host cell cycle arrest, chromosome missegregation, and binucleated phenotype are T. gondii-specific but strain-independent findings.